SỰ BIẾN ĐỔI MỘT SỐ TÍNH CHẤT VẬT LÍ CỦA LÁ CHÈ TRONG QUÁ TRÌNH LÀM HÉO - Chương, Đỗ Văn (Vietnam Journal of Science and Technology, 2012)
THE CHANGE OF SOME PHYSICAL PROPERTIES OF TEA LEAVES DURING THE WITHERING PROCESS Determining the change of some physical properties of tea leaves during the withering process helps technologists and managers establish technological mechanism of properly wilting and crumpling tea leaves for the process of black tea production. Midland tea with one bud and three leaves, which is equivalent to material type B according to Vietnamese standards TCVN 2843-79, it was harvested in district Thanh Ba, province Phu Tho. Then it was withered in the conditions as follows tea layer thickness is 25 cm, wilting air temperature is 34,50C, wilting time is 378 minutes. This process is to determine the transformation of tea block’s area and volume, and to identify tea leaves’ tension, elongation and tearing resistance. The results show that the more young tea leaves are, the more tea leaves’ area decrease, namely: Leaf 1’s area decreases by 67.5% compared with starting material, leaf 2’s area decreases by 45.1% and leaf 3 decreases by 28, 6%. Elongation of leaf 1, 2, 3 stem increases compared with the starting materials is 51.3%, 40.1%, 14.2% - 13.2%. Tearing resistance of leaf 1, 2, 3 also increased compared with starting materials, which is 38.35%, 12.01%, 7.09%, 7.80%. The solid volume of tea block decreases by 29.3% compared with the origin and the porous volume decreases by 50%.